2020
DOI: 10.1038/s41380-020-0843-0
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of antidepressants after remission with antidepressant medication in major depressive disorder: a systematic review and meta-analysis

Abstract: A significant clinical issue encountered after a successful acute major depressive disorder (MDD) treatment is the relapse of depressive symptoms. Although continuing maintenance therapy with antidepressants is generally recommended, there is no established protocol on whether or not it is necessary to prescribe the antidepressant used to achieve remission. In this meta-analysis, the risk of relapse and treatment failure when either continuing with the same drug used to achieved remission or switching to a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 60 publications
1
78
0
3
Order By: Relevance
“…We ultimately included 14 NMAs and 90 MAs, reporting on 15 disorders or groups of disorders. For ADHD, we included three NMAs 5,20,21 and 21 MAs 22‐42 ; for autism, one NMA 43 and 21 MAs 12,44‐63 (including one focusing on comorbid anxiety disorders and autism) 12 ; for depressive disorders, two NMA 7,10 and seven MAs 64‐70 ; for obsessive‐compulsive disorder, one NMA 71 and six MAs 72‐77 ; for anxiety disorders, two NMAs 11,78 and five MAs 12,79‐82 (plus two MAs specific on social anxiety disorder 83,84 ); for enuresis, one NMA 85 and six MAs 86‐91 , for disruptive behavior/dissocial/conduct disorders, five MAs 92‐96 (plus one focusing on youth with comorbid ADHD) 25 ; for eating disorders, one NMA 97 and four MAs 98‐101 ; for schizophrenia spectrum disorders, three NMAs 8,102,103 and two MAs 104,105 ; for bipolar disorder, four MAs 106‐109 ; for tic disorder, two MAs 110,111 ; for Tourette's disorder, two MAs 112,113 ; for encopresis, two MAs 114,115 ; for developmental coordination disorder, one MA 116 ; and for PTSD, one MA 117 .…”
Section: Resultsmentioning
confidence: 99%
“…We ultimately included 14 NMAs and 90 MAs, reporting on 15 disorders or groups of disorders. For ADHD, we included three NMAs 5,20,21 and 21 MAs 22‐42 ; for autism, one NMA 43 and 21 MAs 12,44‐63 (including one focusing on comorbid anxiety disorders and autism) 12 ; for depressive disorders, two NMA 7,10 and seven MAs 64‐70 ; for obsessive‐compulsive disorder, one NMA 71 and six MAs 72‐77 ; for anxiety disorders, two NMAs 11,78 and five MAs 12,79‐82 (plus two MAs specific on social anxiety disorder 83,84 ); for enuresis, one NMA 85 and six MAs 86‐91 , for disruptive behavior/dissocial/conduct disorders, five MAs 92‐96 (plus one focusing on youth with comorbid ADHD) 25 ; for eating disorders, one NMA 97 and four MAs 98‐101 ; for schizophrenia spectrum disorders, three NMAs 8,102,103 and two MAs 104,105 ; for bipolar disorder, four MAs 106‐109 ; for tic disorder, two MAs 110,111 ; for Tourette's disorder, two MAs 112,113 ; for encopresis, two MAs 114,115 ; for developmental coordination disorder, one MA 116 ; and for PTSD, one MA 117 .…”
Section: Resultsmentioning
confidence: 99%
“…to provide prophylaxis. Therefore, following a depressive episode, we recommend maintaining antidepressant treatment for at least six months, and up to one year (see meta‐analysis), 49 and especially if there have been several episodes of illness 50 . Beyond one year there is modest evidence for continuing antidepressant therapy that suggests those receiving antidepressant treatment beyond 12 months (NNT 3.8 CI 3.3–4.6) have significantly fewer re‐occurrences 51 .…”
Section: Maintenance Treatmentmentioning
confidence: 99%
“…In this study, no difference in MDD recurrence was found by hypnotic drug type, suggesting that these advantages may be realized without increasing risk of depression relapse in patients with residual insomnia. However, a recent meta-analysis has reported differences in MDD relapse rates according to class of antidepressant therapy [25].…”
Section: Discussionmentioning
confidence: 99%